Impact of Dietary Crude Protein, Synthetic Amino Acid and Keto Acid Formulation on Nitrogen Excretion - Kim, J.H.; Patterson, P.H.; Kim , W.K. (International Journal of Poultry Science, 2014)
Nitrogen excretion from poultry facilities is one of the environment concerns. High levels of nitrogen excretion in poultry manure could cause eutrophication, nitrate or nitrite contamination in water, ammonia volatilization and acid deposition in the air. Therefore, minimizing nitrogen excretion in poultry manure is essential to maintain a clean environment. In order to minimize nitrogen excretion in manure, precise feed formulation to meet exact birds' nutrient requirements is critical. In this study, an empirical exercise was conducted to evaluate the possibilities of supplementing hydroxy-analogues or keto acids into low protein diets to minimize dietary nitrogen and reduce nitrogen excretion in poultry manure. The results showed that supplementing synthetic amino acids to the 16% CP diet greatly reduced N input (23.6% N) compared to a typical 23% CP corn and soybean meal diet supplemented with synthetic Met and Lys. Utilizing the three hydroxy-analogues with the 16% CP diet reduced nitrogen input further (approximately 3% more) compared to the 16% CP diet supplemented with synthetic amino acids. This empirical exercise showed the opportunities to reduce protein level and utilize synthetic amino acids, keto acids, or amino acid analogues to reduce nitrogen excretion.